INFLUENZA VIRUS EPIDEMIOLOGICAL SITUATION IN THE SOUTH OF WESTERN SIBERIA IN 2011-2012 - I. A. Sobolev; O. G. Kurskaya; E. V. Ivanova; A. G. Durymanov; T. N. Ilyicheva; V. N. Mickheyev; A. M. Shestopalov (Acta Biomedica Scientifica, 2012)
In the result of the monitoring for influenza in the Novosibirsk region during the season 2011-2012 85 strains of influenza virus on the culture of MDCK cells were isolated: 79 strains A (H3N2) and 6 strains of influenza virus B (five strains belonged to the Yamagata line and. 1 strain belonged to the Victoria line). During the entire epidemic season 2011-2012 on the territory of the Novosibirsk region no strains of influenza A (H1N1) pdm09 were allocated. For molecular genetic analysis 3 strains of influenza A (H3N2) were selected. We determined full nucleotide sequence of NA and. HA genes encoding respective surface glycoproteins of influenza virus, as well as the comparative analysis of amino acid sequences of these proteins to the strains of influenza A (H3N2), vaccine strain and. the strain A/Victoria/361/2011 earlier seasons, for which diagnostic serum were obtained.